Novel approaches for the development of direct KRAS inhibitors: structural insights and drug design. (4th March 2022) - Haider, Kashif; Sharma, Anku; Yar, M Shahar; Yakkala, Prasanna Anjaneyulu; Shafi, Syed; Kamal, Ahmed
ABSTRACT: Introduction: Hyperactivated RAS signaling is reported in 13% of all human cancers, in which 80% resulted due to KRAS mutations alone. Direct inhibition of KRAS is an important aspect in treating KRAS-related tumors. Despite the efforts of more than four decades, not many KRAS inhibitors have been successful in obtaining clinical approval, except the very recent FDA approval for sotorasib. In recent years, the understanding of structural insights and allosteric pocket identification at catalytic sites of KRAS are likely to provide an excellent opportunity for the development of much more effective clinical candidates. Area covered: The presented review article mainly summarizes the developments of small molecule KRAS inhibitors as drug candidates and rational approaches that are being utilized for the selective targeting of KRAS signaling in the mutant cancer cells. Expert opinion: After the initial success in targeting the mutant KRAS G12C variants, the search has been shifted to address the challenges concerning the resistance and efficacy of small molecule KRAS inhibitors. However, the contribution of other KRAS mutations at G12V, G13C, and G13D variants causing cancers is much higher than the mutations at G12C. In view of this aspect, specific attention is required to target all other mutations as well. Accordingly, for the development of KRAS targeted therapies, the design of small molecule inhibitors that can inhibit KRAS signaling and as well as target inhibition of other signaling pathways like RAS-SOS and RAS-PI3K has to be explored extensively.